Perasaan Emosional Orang Tua dalam Mendampingi Anak Pada Pembelajaran Daring (Studi Kasus di MTsN 5 Kota Padang) - Dilla Oktaviana; Indri Syarifah; Wahidah Fitriani (QALAMUNA: Jurnal Pendidikan, Sosial, dan Agama, 2021)
This research aims to analyze online learning carried out and explore the emotional feelings of parents in accompanying children's education during online learning. The study was conducted at MTsN 5 Padang City, West Sumatra. This study uses a qualitative method based on a case study approach. The research findings show that; First, online learning at school is realized through the following stages: Teachers, homeroom teachers collaborate with homeroom teachers through the formation of WhatsApp groups. This is intended to reduce misunderstandings between homeroom and homeroom teachers to discuss and exchange ideas. Learning to try to use Zoom Meeting, Google Classroom, and education is also attempted through giving assignments. Second, the procedures that parents try to direct their feelings when accompanying children at home, especially by collaborating with teachers, including mentors to accompany children's tasks, carry out interrelation and closeness with their children.